Rupturas asignificantes: Revisiones críticas en torno al Derecho (2015)
Traditionally, the relationship between the body and the right has beenapproached from the positive instance of the law. To that extent, the bodybecomes a surface on which penalizes the crime evident truths. Contrary to thisperspective, this article aims to rethink the importance of expanding thedialogue with other knowledge law so that opens a thoughtful way to interpret their exercise and introduce another way of studying the body and thecomplexities around same weave.